1986
DOI: 10.1186/1297-9686-18-3-333
|View full text |Cite
|
Sign up to set email alerts
|

Components of prolificacy in hyperprolific Large White sows compared with the Meishan and Large White breeds

Abstract: SummaryWe identified the most prolific sows in French Large White herds and 17 hyperprolific sows (HLW) were bought whose average litter size on 3 farrowings was 16.5 piglets born alive, i.e. a superiority of 5.3 piglets per litter over their contemporaries. In 1 to 3 subsequent pregnancies we compared ovulation and embryonic mortality rates of 10 HLW with those of 10 Large White (LW) and 7 Meishan (MS) sows. The ovulation rate of HLW was significantly higher than that of LW (-!-5.3) and MS ( + 5.7). The ovula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
28
2
6

Year Published

1990
1990
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(37 citation statements)
references
References 7 publications
1
28
2
6
Order By: Relevance
“…Comparisons in France show no difference between the breeds or a greater number of ovulations in the large white females (Bolet et al, 1986;Bazer et al, 1988). By contrast, in the UK, the Meishan females have usually been observed to have a greater number of ovulations than large white females, both as gilts and sows, in experiments involving several hundred observations Ashworth et al, 1992; the present study).…”
Section: Introductioncontrasting
confidence: 47%
“…Comparisons in France show no difference between the breeds or a greater number of ovulations in the large white females (Bolet et al, 1986;Bazer et al, 1988). By contrast, in the UK, the Meishan females have usually been observed to have a greater number of ovulations than large white females, both as gilts and sows, in experiments involving several hundred observations Ashworth et al, 1992; the present study).…”
Section: Introductioncontrasting
confidence: 47%
“…In both France (Bidanel et al, 1989) and the UK (Haley and Lee, 1990) (Bolet et al, 1986;Bazer et al, 1988;Bidanel et al, 1990a), whereas studies on the UK Meishan sample have found signifi¬ cantly higher ovulation rates in both gilts and sows than in Large White females Haley and Lee, 1990;Wilmut et al, 1992). With no advantage to the Meishan in ovulation rate, the prolificacy of the French sample compared with the Large White breed is due to enhanced pre¬ natal survival (Bolet et al, 1986;Bazer et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…With no advantage to the Meishan in ovulation rate, the prolificacy of the French sample compared with the Large White breed is due to enhanced pre¬ natal survival (Bolet et al, 1986;Bazer et al, 1988). Prenatal survival in the Meishan breed in the UK is only slightly greater than in the Large White breed (Haley and Lee, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Puberty occurs at about 3 months, thus much earlier than in European pig breeds (6-7 months). Average litter sizes are 30-40% higher than those of contemporary Large White pigs (Bolet et al, 1986; (Bidanel and Legault, 1986;Bazer et al, 1988; On day 20 of lactation, blood samples (3 ml) were taken for 6 h at 15-min intervals for analysis of LH. On day 22 all sows received an im injection of 15 5 og oestradiol benzoate (OB, Progynon B Oleosum, Schering)/kg body weight.…”
mentioning
confidence: 99%